(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The aim of this study was to examine whether the positive response in milk production and nutritional quality of milk in local dairy cows in Khulna fed with sugar beet silage. 18 dairy cows of local breed and cross-breed were used in as 2x2 Latin square design experiments with 2 rations: (1) control with wheat bran as energy source and (2) treatment group with sugar beet silage as energy source. A total of 72 milk samples were collected to evaluate fat, solids not fat, (SNF), total solids (TS), protein, lactose. The milk production and nutritional quality of sampled milk for both group 1 and 2, milk yield (2.04%±1.20 and 2.28%±1.52%),fat (3.47%±1.64% and 3.49%±1.71%), SNF (8.20%±0.69% and 8.17±0.95), TS (12.39%±1.89% and 12.37%±2.20), protein (3.61%±0.50% and 3.66%±0.90%), lactose (4.55%±0.53% and 4.52%±0.78%), were not significant (p>0.05).The correct lactometer reading for both locations was 29.83%±2.11% and 29.41%±3.16%, respectively. Nutritional composition of sample milk in local and cross breed, milk yield (1.31±0.18 and 3.86±1.09), fat (4.101±1.43 and 2.26±1.42), SNF (8.31±0.87 and 7.94±0.66), TS (13.11±1.91 and 10.91±1.41), Protein (3.62±0.78 and 3.67±0.60), Lactose (4.67±0.52 and 4.26±0.83) were statistically significant ((p>0.05).) In conclusion, sugar beet silage feeding has no negative effect and milk production and milk quality. Feeding ensiled sugar beets as an alternative energy-rich, highly palatable feedstuff to ruminants in Bangladesh seems therefore to be promising. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 166-172